Virtual world atlas (Rugeley : Focus Multimedia Limited, 2002)
Travel anywhere on the planet without restraint, bookmark places of interest, take snap shots of your favourite places and animals and include them in your photo album, easy to use search facility, 23 demos featuring fly throughs in realistic 3D video mode, useful help screen on how to use the various icons, shows the latitude and longitude of your current position in the world, change the position of the sun and moon to view the planet at different times of the day.
Ελάχιστες απαιτήσεις συστήματος: Windows 95/98/ME/2000/XP.
Keywords: CD-ROMs.; Atlases -- Interactive multimedia